Dinamika Penggunaan Lahan dan Pemetaan Risiko Bencana Letusan Gunung Bromo Menggunakan Citra Sentinel-2 di Kabupaten Probolinggo, Indonesia - Dody Feryanto Kurniawan; Surjono; Fauzul Rizal Sutikno (Postgraduate, University of Mataram, 2026)
This study examines the spatial relationship between land use/land cover (LULC), volcanic hazard zones, and soil conditions in the Mount Bromo area of Probolinggo Regency, East Java, Indonesia. It aims to identify dominant LULC classes, quantify their overlap with volcanic hazard zones, and provide a spatial basis for risk-sensitive land-use planning. Sentinel-2 imagery was classified into four classes: vegetation, open land, agricultural land, and built-up area, and the results were evaluated using a confusion matrix. The classification achieved an overall accuracy of 81.97% and a kappa coefficient of 0.82, indicating reliable performance for regional-scale analysis. Agricultural land was the dominant class, covering 121,477.01 ha or 71.62% of the study area. Volcanic hazard zonation shows that 5,439.86 ha or 3.21% of Probolinggo Regency falls within Mount Bromo’s low-, moderate-, and high-hazard zones, including 941.66 ha or 0.56% in the high-hazard zone. Overlay analysis revealed that 212.39 ha of agricultural land and 16.33 ha of built-up area are located in the high-hazard zone, while 389.45 ha of agricultural land and 9.34 ha of built-up area remain in the moderate-hazard zone. Hazardous zones also spatially coincide with Mollic Andosols, indicating that volcanic risk overlaps with productive soils. These findings show that productive land and settlement-related land use are still not fully aligned with volcanic hazard conditions, highlighting the need for risk-sensitive spatial planning and adaptive land management.